2023
DOI: 10.2147/idr.s417968
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcosis in Southern China: Insights from a Six-Year Retrospective Study in Eastern Guangdong

Hazrat Bilal,
Dongxing Zhang,
Muhammad Shafiq
et al.

Abstract: Objective Cryptococcosis is a fatal infection that can affect both immunocompetent and immunocompromised patients, and it is little understood in China’s various regions. This research aimed to look at the epidemiology, risk factors, and antifungal susceptibility pattern of Cryptococcus neoformans in eastern Guangdong, China. Methods A six-year (2016–2022) retrospective study was conducted at Meizhou People’s Hospital, China. Demographical, cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…In mainland China, 15.7% of the cryptococcosis patients were AIDS or HIV-infected [ 26 ], while 60% of PC cases were diagnosed in immunocompetent non-HIV patients [ 27 ]. A recent study reported the most common types of Cryptococcus infections in Southern China were cryptococcal meningitis, cryptococcal fungemia, and PC, and only 12 out of the 170 patients had autoimmune disorders [ 28 ]. According to the local Health Department in the Ningbo city, there were 9 cases of adult with PC over the past year, all with normal immune function, and the present case was the only case of PC in child.…”
Section: Discussionmentioning
confidence: 99%
“…In mainland China, 15.7% of the cryptococcosis patients were AIDS or HIV-infected [ 26 ], while 60% of PC cases were diagnosed in immunocompetent non-HIV patients [ 27 ]. A recent study reported the most common types of Cryptococcus infections in Southern China were cryptococcal meningitis, cryptococcal fungemia, and PC, and only 12 out of the 170 patients had autoimmune disorders [ 28 ]. According to the local Health Department in the Ningbo city, there were 9 cases of adult with PC over the past year, all with normal immune function, and the present case was the only case of PC in child.…”
Section: Discussionmentioning
confidence: 99%